Eksplorasi dan Identifikasi Cendawan Penyebab Penyakit Tanaman Sawi Pakcoy (Brassica rapa L.) - Latifah, Nurul; Salamiah, Salamiah; Soedijo, Samharinto (Agroekotek View, 2023)
Research has been conducted with the title Exploration and Identification of Fungus Causing Disease Sawi Pakcoy Plant (Brassica rapa L). This study aims to find out the types of diseases and symptoms that attack in pakcoy plants (Brassica rapa L). This research was conducted in Guntung Payung, Landasan Ulin District, Banjarbaru City, South Kalimantan (Field) and Agroecotechnology Production Laboratory of The Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru. For field research conducted by visual observation of disease attack symptoms or by looking at the symptoms seen in plants in the field, followed by identifying disease-causing pathogens in the laboratory. Field sampling was randomly taken in four crop plots. Samples taken in the form of parts of plants affected by the disease. The results showed there are three types of mushrooms that attack the plant of mustard pakcoy, fungus found to be pathogenic and also parasites that cause mustard pakcoy to grow not optimally and also cause death. Fungus who attacked in each map is Fusarium sp., Phytophthora sp. and Curvularia sp.